1978
DOI: 10.1159/000158161
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Response of Three Embryologically Distinct Segments of the Isolated Canine Posterior Vena cava to Vasoactive Substances

Abstract: The canine posterior vena cava was excised and divided into three embryologically distinct segments: segment A (supradiaphragm), segment B-C (intra-hepatic and that between liver and renal veins), and segment D (infrarenal). Circular and longitudinal strips were cut from each segment, suspended in Krebs bicarbonate solution and isometric tensions were recorded. The responses to six vasoactive agents, as well as transmural neural stimulation were studied. Maximum tension and ED50 were obtained for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
4
21
0
Order By: Relevance
“…The second contraction induced by 5-hydroxytryptamine is due to its action on the sympathetic nerves (2). In the present study, remarkable second contractions were observed in the cephalic, portal, mesenteric and lateral saphenous veins and segment B-C of the inferior vena cava.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The second contraction induced by 5-hydroxytryptamine is due to its action on the sympathetic nerves (2). In the present study, remarkable second contractions were observed in the cephalic, portal, mesenteric and lateral saphenous veins and segment B-C of the inferior vena cava.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to the findings in the twelve veins, the analyses included the data of three segments of the inferior vena cava which were obtained in the previous study (2). The three segments were segment A (supradiaphragm), segment B-C (intrahepatic and that between the liver and renal veins) and segment D (infrarenal).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few reports de scribing the endothelium-dependent re sponses of veins (3,4). In previous papers, we repeatedly indicated that the canine venous system consists of veins characteristically different in pharmacological responses (5)(6)(7)(8)(9). Therefore, in the present study, distribution of endothelium-dependent relaxation re sponses in the venous system was inves tigated by using 15 canine veins selected systematically (5,6).…”
mentioning
confidence: 91%
“…These three veins are embryologically related to the digestive tube, being characterized by the presence of massive longitudinal muscles, spontaneous rhythmic contractile activity, as well as cholinergic excitatory innervation (1 4). Some evidences of the innervation ob tained by in vitro and in vivo experiments were reported (3,(5)(6)(7). Additional findings were reported by Uematsu et al (8).…”
mentioning
confidence: 79%